Syringomyelia with atypical presentation (Bangladesh Medical Journal Khulna, 2012)
A 50 years old male patient was admitted in Khulna Medical College Hospital with grade-III weakness of both upper limbs and grade-IV weakness of both lower limbs, marked wasting of muscles in upper back and shoulder girdle region. There was no fasciculation, no pyramidal signs and no sensory loss. All routine investigations including NCS and EMG were normal. MRI of cervical and dorsal spine revealed a large syrinx extending from the cervico-medullary junction to the sixth dorsal spine with herniation of cerebellar tonsil through foramen magnum. With these findings the case was diagnosed as syringomyelia with atypical presentation. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13019 Bang Med J (Khulna) 2010; 43: 21-22